2009
DOI: 10.1080/09638280902874170
|View full text |Cite
|
Sign up to set email alerts
|

Hand function and Disability of the Arm, Shoulder and Hand in Charcot-Marie-Tooth disease

Abstract: Reduced hand function in CMT was found at different dimensions according to the International Classification of Functioning, Disability and Health (ICF). We suggest that DASH can be used in persons with CMT, though clinicians should be aware that patients might score lower than expected, possibly because of a long process of adaptation when learning to live with a slowly progressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…1,9,14,26 Slightly higher correlations were reported between hand function as measured by a performance based tests (Sollerman) and grip and pinch strength, dexterity, and sensation but the correlations were still mainly in the moderate range 1,26 while good to excellent correlations were reported by Eklund et al, between the DASH and grip strength and the Nine-hole Peg Test. 12 The lower correlations found in our study could be due to the smaller sample size or older age of our sample. Only the Videler et al study 26 included people with only one subtype of CMT; the samples in the other studies included participants with different subtypes.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…1,9,14,26 Slightly higher correlations were reported between hand function as measured by a performance based tests (Sollerman) and grip and pinch strength, dexterity, and sensation but the correlations were still mainly in the moderate range 1,26 while good to excellent correlations were reported by Eklund et al, between the DASH and grip strength and the Nine-hole Peg Test. 12 The lower correlations found in our study could be due to the smaller sample size or older age of our sample. Only the Videler et al study 26 included people with only one subtype of CMT; the samples in the other studies included participants with different subtypes.…”
Section: Discussionmentioning
confidence: 50%
“…11 Overall manual dexterity is also diminished, as people with CMT manipulate one-inch wooden cubes (Box and Block Test) much slower than controls and require 50% more time, on average, to place and remove onequarter-inch diameter wooden dowels in a peg board (Nine-Hole Peg Test). 12 Diminished sensation, including pain, temperature, vibration, and proprioception, is also a typical symptom of CMT. 6,13 The few studies that have examined the impact of impairments in the hand on functional activities in people with CMT reported that dexterity, hand strength, and sensation reported outcome that may have the potential to assess hand function in people with CMT is the Manual Ability Measure (MAM-36).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory impairments were assessed in terms of the level and severity of pain, temperature, vibration and position, then pain and vibration senses were compared. In order to determine physical disability we used three scales, a functional disability scale (FDS) (Birouk et al, 1998), a CMT neuropathy score (CMTNS) (Shy et al, 2005), and 9-hole peg test (9-HPT) (Eklund et al, 2009). Disease severity was determined for each patient using a nine-point FDS, which was based on the following criteria: 0, normal; 1, normal but with cramps and fatigability; 2, an inability to run; 3, walking difficulty but still possible unaided; 4, walking with a cane; 5, walking with crutches; 6, walking with a walker; 7, wheelchair bound; and 8, bedridden.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…The test has been validated in all age groups and has high inter-rater and test-retest validity. The 9-HPT shows concurrent and convergent validity, and the measure appears sensitive to change in adults with neuromuscular and musculoskeletal disorders 50, 51 . Both adult and pediatric norms are available 48, 49 .…”
Section: Selected Assessments For Nmdmentioning
confidence: 99%